PELAKSANAAN ANGGARAN PENERIMAAN DAN PENGELUARAN DANA DESA DALAM MENUNJANG PEMBANGUNAN DESA DI DESA TOMBULANG KECAMATAN PINOGALUMAN KABUPATEN BOLAANG MONGONDOW UTARA - Kristiani, Kristian; Pelleng, Frendy A. O.; Manopo, W. S. (JURNAL ADMINISTRASI BISNIS, 2017)
This researce based on the importance of the invorvement of all elements of village administration in Tombulang village of North Bolaang Mongondow Regency, in maximizing village revenues sourced from village funds to support development. To that end, the village government must understand how the implementation og budget of revenues and expenditures of village fund in supporting development. This study aims to find out how the implementation of budget revenue and expenditure of village funds in support village development. Accourding to Government Regulation Number 60 year 2014, Village funds are funds sourced from the State Revenue and Expenditure Budget in the designated for the villages transferred through the Regional Revenue Budgets and are used to finance the implementation of governance, development and community and community empowerment. This research used descriptive qualitative research methods, data analysis techniques used in this study is the percentage of data analysis. Informant research amounted to 3 people and data collection technique is documentation study, interview, and observation. The focus of the research is the accountability report of Village Revenue and Expendeture year 2015 and 2016. The results show that the role of village funds in the development of Tombulang Village has been well realized although there are some things that are unclear in the implementation of APBDesa and public participation and the role of government that has not been optimal. Briefly, the active role, tranparency and responsibility of the apparatus involvet in managing village funds is needed to support community development in the village and impact on the welfare of the community. In this case the village government in demand to be more involving the community in submetting the proposet plan of preparation of APBDesa and priotize the principle of honesty in order to avoid misunderstanding. Keywords: Village Fund, Budeget, and Village Development